THE EFFECT OF ORGANIZATIONAL CLIMATE AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF EMPLOYEES AT PT.EXPRAVET NASUBA - Vinesa Intan Savira; Nina Siti Salmaniah Siregar; Patisina (RADJA PUBLIKA, 2023)
The research objective was to determine the effect of organizational climate on organizational citizen behavior in PT.Expravet Nasuba Medan's employees, to determine the effect of organizational commitment on organizational citizen behavior in PT.Expravet Nasuba Medan's employees, to determine the effect of organizational climate and organizational commitment on organizational citizen behavior in PT employees Expravet Nasuba Medan?. This research is a quantitative research method. This section explains matters related to research methods such as research variables, operational definitions, populations, samples, sampling techniques, research measurement tools, data collection procedures, scaling, discriminatory power and reliability of measuring instruments, classical assumption tests, and hypothesis testing. . This research will be tested and implemented on employees at PT. Expravet Nasuba with a minimum working period of one year, and this research will begin in July 2023, the entire population of production employees at PT. Expravet Nasuba Medan. The overall population is 168 production employees. Sampling was carried out using the nonprobability sampling design technique, namely by using purposive sampling. The total sample in this study amounted to 120 employees. The data collection method is a method used by researchers to obtain the data used is a Likert scale. The data is processed using SPSS software. Data analysis techniques namely the validity and reliability of measuring instruments, validity tests, reliability tests, descriptive statistics, classical assumption tests and hypothesis testing. The results showed that there was a significant positive influence between organizational climate on organizational citizenship behavior of employees of PT. Nasuba expravet, with a predictor determinant coefficient value (R^2) of 0.326, which means that organizational climate contributes 32.6 percent to organizational citizenship behavior. This means that the higher the organizational climate, the higher the organizational citizenship behavior. Conversely, the lower the organizational climate, the lower the organizational citizenship behavior. There is a significant positive influence between organizational climate on organizational citizenship behavior of employees of PT. Nasuba expravet, with a predictor determinant coefficient value (R^2) of 0.421, which means that organizational climate contributes 42. 1 percent affects organizational citizenship behavior.